Pengaruh Pengolahan Dampo Pisang Melalui Kegiatan P5 terhadap Kreativitas Siswa Kelas 4 SD Integral Al Bayan Hidayatullah Makassar - -Besse, Besse Siti Halima; Prabu Setiawan , Ince; Hastati, Sri (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstract: This study aims to analyze the influence of banana dampo processing through the Pancasila Student Profile Strengthening Project (P5) on the creativity of fourth grade students of SD Integral Al-Bayan Hidayatullah Makassar. Creativity is an important aspect of student development, which can be developed through project-based learning activities. Banana dampo processing as a form of project in P5 activities was chosen because of its relevance to local wisdom and its ability to involve various aspects of students' skills, such as cooperation, innovation, and motor skills. This study uses a quantitative approach with the type of experimental research with a one-group pretest posttest design using the subject, namely class IVB as many as 21 students as an experimental class. Data was collected through observation, creativity test instruments (pretest and posttest), and documentation. The data analysis techniques used were descriptive statistical analysis and inferential analysis consisting of normality, homogeneity, and hypothesis tests using independent sample t-tests to see a significant influence between banana dampo processing activities and the level of student creativity. The results of this study show that banana dampo processing activities in P5 activities have a significant influence on increasing the creativity of grade IVB students of SD Integral Al-Bayan Hidayatullah. Students involved in this project show better creative thinking skills, especially in terms of idea development, problem-solving, and product innovation.